2004
DOI: 10.1901/jaba.2004.37-323
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dense‐to‐lean and Fixed Lean Schedules of Alternative Reinforcement and Extinction

Abstract: Behavior-reduction interventions typically employ dense schedules of alternative reinforcement in conjunction with operant extinction for problem behavior. After problem behavior is reduced in the initial treatment stages, schedule thinning is routinely conducted to make the intervention more practical in natural environments. In the current investigation, two methods for thinning alternative reinforcement schedules were compared for 3 clients who exhibited severe problem behavior. In the dense-to-lean (DTL) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 19 publications
4
67
0
Order By: Relevance
“…In our review, we found five studies describing eight applications of FCT that used multiple schedules as a means of thinning reinforcement schedules and maintaining low rates of problem behavior (see Table). In some of the applications (5 of 8), the use of multiple schedules resulted in the successful achievement of treatment goals with FCT and extinction without supplemental treatment components (Hagopian, Toole, Long, Bowman, & Lieving, 2004;Hanley et al, 2001;Jarmolowicz et al, 2009). However similar to the previous two schedule-thinning methods, for some applications (3 of 8), treatment goals were not met until supplemental components were added (e.g., adding competing or alternative stimuli; Fisher et al, 1998;Hagopian et al, 2005).…”
Section: Multiple Schedulesmentioning
confidence: 95%
See 3 more Smart Citations
“…In our review, we found five studies describing eight applications of FCT that used multiple schedules as a means of thinning reinforcement schedules and maintaining low rates of problem behavior (see Table). In some of the applications (5 of 8), the use of multiple schedules resulted in the successful achievement of treatment goals with FCT and extinction without supplemental treatment components (Hagopian, Toole, Long, Bowman, & Lieving, 2004;Hanley et al, 2001;Jarmolowicz et al, 2009). However similar to the previous two schedule-thinning methods, for some applications (3 of 8), treatment goals were not met until supplemental components were added (e.g., adding competing or alternative stimuli; Fisher et al, 1998;Hagopian et al, 2005).…”
Section: Multiple Schedulesmentioning
confidence: 95%
“…Hagopian et al (2004) compared the effects of progressive schedule thinning (similar to that described above) to an abrupt shift to the terminal schedule. For one of two cases, the clinical goal was attained more rapidly in the abruptly shifting condition than in the progressive thinning condition.…”
Section: Abruptly Shifting To the Terminal Schedulementioning
confidence: 99%
See 2 more Smart Citations
“…Although it is described here for use during teaching situations, this type of multipleschedule procedure has been used in the treatment of severe problem behavior (e.g., Fisher, Kuhn, & Thompson, 1998;Hagopian, Toole, Long, Bowman, & Lieving, 2004;Hanley, Iwata, & Thompson, 2001;Neidert, Iwata, & Dozier, 2005) and in teaching verbal skills to children with autism (Sidener, Shabani, Carr, & Roland, in press). One similarity that exists among these studies is that all involved the presentation of both an S+ (a discriminative stimulus correlated with reinforcement) and an S2 (a discriminative stimulus correlated with extinction).…”
mentioning
confidence: 99%